Purple grain colour genes in wheat - Khlestkina E.; Shoeva O.; Börner A.; Gordeeva E. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Purple colour of wheat grain is caused by accumulation of anthocyanins in the pericarp. Potential health benefits and adaptability may be the reason for a renewed interest in wheat with high anthocyanin content. Genetic bases underlying purple grain character as well as some practical aspects are reviewed in this paper. Two complementary dominant genes control purple pericarp coloration in both durum (Triticum durum Desf., 2n = 4x = 28) and bread (T. aestivum L., 2n = 6x = 42) wheat. In durum wheat, these genes are mapped to be on chromosomes 2A (Pp3) and 7B (Pp-B1), whereas in bread wheat they are located on chromosomes 2A (Pp3) and 7D (Pp-D1). Functional alleles of at least one of the two complementary genes determining purple pericarp exist in Ae. speltoides, Ae. tauschii and T. timopheevii – the species, in which purple-grained plants have never been described. The wheat Pp-1 and Pp3 genes regulate transcription of the anthocyanin biosynthesis structural genes and may encode transcription regulatory factors that belong to the MYB- and MYC-like superfamilies, respectively. Their orthologues were cloned in maize, rice and barley and can be used for homology-based cloning of wheat Pp-1 and Pp3. Usefulness of microsatellite markers closely linked to the Pp genes for marker-assisted selection has been demonstrated.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)